Food flavors and chemistry advances of the new millennium - Spanier, A. M. 1948- (Royal Society of Chemistry, 2001)
This product is not available separately, it is only sold as part of a set. There are 750 products in the set and these are all sold as one entity. Food may be nutritious, visually appealing and easy to prepare but if it does not possess desirable flavors, it will not be consumed. Food Flavors and Chemistry: Advances of the New Millennium primarily focuses on food flavors and their use in foods. Coverage also includes other important topics in food chemistry and production such as analytical methods, packaging, storage, safety and patents. Positive flavor notes are described, including ways of enhancing them in food. Conversely, methods for eliminating and reducing undesirable flavors are also proposed. Packaging aspects of foods, with respect to controlling sensory attributes, appearance and microbiological safety are discussed in detail. There is also a section concentrating on the most recent developments in dairy flavor chemistry. This book will be an important read for all postgraduate students, academics and industrial researchers wanting to keep abreast of food flavors and their chemistry.
"The second annual George Charalambous Memorial Symposium was 10th in the series of International Flavor Conferences ... held 2-7 July 2000 on the Greek island of Paros"--Pref.
Keywords: Flavor -- Congresses.; elektronické knihy; electronic books